2018
DOI: 10.16965/ijims.2018.115
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Profile of the Gastrointestinal Polyps in Kashmir Valley

Abstract: Introduction: A gastrointestinal (GI) polyp is a discrete mass protruding into the lumen of GI Tract projecting above the plane of the mucosal surface .Polyp may be neoplastic and neo-neoplastic in nature. Determining the potential risk of malignancy of the polyp is very important for the purpose of line of treatment. The polyp size and histological types are important factors for development of cancers in polyps.Materials and Methods: This was a five year observational study conducted from 2012-2016. All the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…In regards to associated dysplasia in polyps , Tony J et al 3 showed that severe dysplasia was found in 43% of polyps with villous pattern and 12% of those with tubular pattern however in this study only 1.8 % of polyps with pure tubular pattern had high grade dysplasia while 30.4 % with tubulovillous variety (p<0.001) had high grade dysplasia suggesting that villous component increases the neoplastic potential of the polyps.Other Indian studies by Ashraf et al 12 from Kashmir and Amarapurkar series 10 from Mumbai also had similar finding of increasing severity of dysplasia with presence of villous component.…”
Section: Discussion:-supporting
confidence: 59%
“…In regards to associated dysplasia in polyps , Tony J et al 3 showed that severe dysplasia was found in 43% of polyps with villous pattern and 12% of those with tubular pattern however in this study only 1.8 % of polyps with pure tubular pattern had high grade dysplasia while 30.4 % with tubulovillous variety (p<0.001) had high grade dysplasia suggesting that villous component increases the neoplastic potential of the polyps.Other Indian studies by Ashraf et al 12 from Kashmir and Amarapurkar series 10 from Mumbai also had similar finding of increasing severity of dysplasia with presence of villous component.…”
Section: Discussion:-supporting
confidence: 59%